Behavioral Analysis of Single-use Plastic Consumption in Cairo - Laura Maria Diaz Ospina (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Plastic pollution is a huge environmental and urban problem in Cairo. The overconsumption of single-use plastic bags (SUPB) and their inadequate disposal are significant contributors to it. The aim of this research is to unveil the behaviors and factors that encourage and discourage the use of SUPB among Cairenes. The research analyzed environmental awareness and the willingness to adopt pro-environmental behaviors. The methodology used is based on the Theory of Planned Behavior and S.H.I.F.T Framework. The results demonstrate that people are environmentally conscious and willing to change their behavior, yet they consume a considerable amount of SUPB. Furthermore, there is a gap between what people say and how they act. This could be changed through different factors such as Social Influence, Tangibility, Positive Emotion, and Policies. These factors can potentially influence the reduction of SUPB and encourage the adoption of pro-environmental behaviors and policies.